Riddles on YouTube: Investigating the potential to engage viewers in reflective thinking - Petr Lebedev; Manjula Devi Sharma (Research in Learning Technology, 2019)
Linear videos continue to be useful technologies for both formal and informal learning. The advent of YouTube has seen the rise of educational channels engaging millions of viewers informally, in the spirit of ‘lifelong learning’. This article investigates the potential of a particular kind of video to engage viewers in reflective thinking. The premise is that viewers, followers who find the channel worthwhile or interesting, should reflect, affirming or changing their answers. The channel Veritasium, with more than 5 million subscribers at the time of this study, posed four questions as ‘riddles’, and then a week later provided solutions. A survey appended to the solutions video was completed by 2220 respondents. About 16%–43% of respondents across all riddles indicated that their answer was correct or that they changed their answer, and 49%–73% reported to have changed their answers. The reasons for not changing answers were inductively coded for each riddle. The emergent categories were the same for the different riddles, from outward focused to inward focused, matching the types of reflective thinking in the extant literature. The responses illustrated how the riddles engaged the viewers in reflective thinking in this social media informal learning context.